STRUKTUR PENYAJIAN TARI NGAJAT LESUNGPADA GAWAI BATU DAYAK IBAN KABUPATEN BENGKAYANG - Violeta, Veronica Mega; Fretisari, Imma; Ismunandar, Ismunandar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is depended on the unique and the special of Ngajat Lesung folk dance that made the reseacher interested to done the research about The Structure to Present Tari Ngajat Folk Dance in Gawai Batu of Dayak Iban Peoples in Seluas rural of Seluas District and Bengkayang Regency. The purpose of this research is to describe the structure to present Ngajat Lesung folk dance.Method that used in this research is descriptive method with qualitative research type. The research approach in this research is Choreography Approach.The data results are interview, observation, and documentation. Techniques of data validation in this research are using obervation extension and triangulation sources. Techniques of data analysis in this research are data reduction, data presentation, and verification. Ngajat Lesung Dance has structures which consist of initial, middle, and end movements. Other elements contained in the structure include, Floor design, Top design, Dance Dynamics, group composition, the theme, accompaniment, make up and clothing, dance property, place of performance, The result of this research is expected to be implemented in the teaching of art and culture subject to the VIII grade of the first semester one. Keywords: Presentation Sturcture, NgajatLesungDance, Seluas Subdistrict.